PENINGKATAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH RUMAH TANGGA - Cahyo Ismoyo; MR. Khairul Muluk; Choirul Saleh (REFORMASI, 2015)
Waste problem in Indonesia has become complicated and difficult problem to solve. One attempt to overcome this problem is to change the method of waste management from the pipe line to the management on the basis of the 3Rs (reduce, reuse, recycle). It will not be achieved without the participation of the community in the planning, implementation, management and evaluation. On the other hand planning with community involvement (participatory planning) has not found its ideal form, the low level of participation has always been a major issue. Community development is seen as a concept that is used in addition to facilitate participation, the concept is also used to increase public participation. In the process of community development, it aims to improve the capacity of community decision-making that is useful to overcome the problem by utilizing existing resources. Through this process then the solution for issue of waste in the planned housing is planned.